2017
DOI: 10.1097/sla.0000000000002365
|View full text |Cite
|
Sign up to set email alerts
|

Wide Variation and Overprescription of Opioids After Elective Surgery

Abstract: The majority of patients were overprescribed opioids. Significant prescribing variation exists that was not explained by patient factors. These data will guide practices to optimize opioid prescribing after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
214
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(225 citation statements)
references
References 22 publications
3
214
2
1
Order By: Relevance
“…A number of investigations have demonstrated that surgeons overprescribe opioids at discharge, with wide variations in prescribing practices among providers 197. It is generally accepted that 6% of opioid-naive patients will become chronic opioid users after surgery, while the rate is as high as 21% for those who require chemotherapy after surgery 198 199.…”
Section: Resultsmentioning
confidence: 99%
“…A number of investigations have demonstrated that surgeons overprescribe opioids at discharge, with wide variations in prescribing practices among providers 197. It is generally accepted that 6% of opioid-naive patients will become chronic opioid users after surgery, while the rate is as high as 21% for those who require chemotherapy after surgery 198 199.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially the case as the overprescription of this drug class has contributed to the creation of a national crisis in the USA and other parts of the world 27. Non-opioid constituents of multimodal analgesia ideally avoid opioid-related side effects, development of tolerance, and necessity for distribution of outpatient opioid prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the 7 day follow up data has been demonstrated to give a reasonable estimate of overall outpatient opioid use because the majority of patients in the study did not require a refill after mastectomy (refill rate 31.5%) and the time to refill was a mean of 8.38 days (median 7 days). Similarly, a study from Mayo Clinic found that less than 10% of patients undergoing either breast‐conserving surgery or mastectomy required a prescription refill after 30 days from the initial prescription . Lastly, the use of PVB was at the discretion of the surgeon and anesthesiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous recent publications have examined opioid use after general surgery procedures, which include some breast surgical oncology (BSO) operations, there is a paucity of data examining opioid use for the range of BSO procedures performed . In addition, published research does not address surgeons’ impressions of opioid need after breast surgery, which can be a driver of prescription practice.…”
Section: Introductionmentioning
confidence: 99%